Osobennosti predstartovoi razminki i massazha plovtsov vysokoi kvalifikatsii - Aikina, L. I. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The author recommends some holds for prestart massaging of swimmers at the period of their worming up. The physiological and pedagogical substantiations of massage's holds and their distribution over the stages of worming up are represented. The author recommends the accents to different muscle groups for worming up in various styles of swimming.